Effect of Enzyme Supplemented Cassava Root Sieviate on Egg Quality Gut Morphology and Performance of Egg Type Chickens - Aderemi, F.A.; Lawal, T.E.; Alabi, O.M.; Ladokun, O.A.; Adeyemo, G O. (International Journal of Poultry Science, 2006)
Enzymic supplementation of cassava root sieviate (CRS) in cassava –based diet was investigated in layers. One hundred and twenty laying birds of Nera strain at 22 weeks old were divided into twelve groups and randomly assigned to the four groups of diets. It lasted for 84 days at the teaching and research farm of the university of Ibadan Nigeria. Results of control avizyme and dried pure yeast (DPY) supplemented diet were similar and significantly (P< 0.05) higher than unsupplemented cassava diets. Feed intake revealed that layers fed cassava-based diet had lower consumption when compared to those fed control. Feed conversion however showed that those layers on DPY supplemented diet were significantly (P< 0.05) better than others. Final body weight of the layers showed that those on control were significantly (P< 0.05) heavier than others. The kidney, heart, abdominal fat and oviduct of layers cassava diet either supplemented or not were significantly (P< 0.05) reduced when compared with others on control. The gizzard weight of layers fed unsupplemented and supplemented was also significantly (P< 0.05) increased. No mortality was recorded during the feeding trial. Considering egg production layers on control performed better than others, economically DPY diet ranked second to control.